A new approach to treat carbapenem resistant Acinetobacter baumannii (CRAB) bacteremia using sulbactam-avibactam combination: A case report - Sameer Alzaidi; Manahil Alharthi; Hams Alshammamri; Yasir Almalki; Osama Almalki; Shahad Alqahtani; Mohammed Alosaimi; Nouran Althumali (IDCases, 2025)
Carbapenem resistant Acinetobacter baumannii (CRAB) infections are serious disease that can be fatal. Only a few therapeutic options are available, with conflicting data for their meaningful clinical outcomes. Here, we report a case of 83-year-old female CRAB bacteremia that was successfully treated with ceftazidime-avibactam and ampicillin-sulbactam combination after failing guidelines directed therapy.